Outcome of surgical treatment of pelvic osteosarcoma : Hospital Universiti Sains Malaysia experience - Sharifudin, Mohd Ariff; Wan, Zulmi; Wan Ismail, Wan Faisham Numan; Mat Zin, Nor Azman; Mohamed Amir, Nawaz Hussain (Malaysian Orthopaedic Association, 2013)
We reviewed the surgical treatment and outcomes of 13 patients with pelvic osteosarcoma treated in our centre in the past decade. The study sample included 9 males and 4 females with a mean age of 28.1 years. Four patients had ileal lesions, five had acetabulum lesions, one had a ischiopubis lesion, and three had involvement of the whole hemipelvis. Seven patients presented with distant metastases at diagnosis. Limb salvage was performed in 6 patients and amputation in 7. In 60% of cases in the limb salvage surgery group, we attempted wide resection with positive microscopic margin compared to only 16.7% in the amputation group. Local recurrence was higher in the limb salvage group. Overall survival was 18 months for mean follow up of 14.8 months. Median survival was 19 months in the limb salvage group compared to 9 months in amputation group. The outcome of surgical treatment of pelvic osteosarcoma remains poor despite advancements in musculoskeletal oncology treatment.